Bronchial vascular remodelling in patients with COPD and its relationship with inhaled steroid treatment. Issue 12 (6th September 2009) - Zanini, A; Chetta, A; Saetta, M; Baraldo, S; Castagnetti, C; Nicolini, G; Neri, M; Olivieri, D
Abstract : Background: Only a few studies have evaluated microvascular changes and proangiogenetic mediators in the bronchial mucosa of patients with chronic obstructive pulmonary disease (COPD), and the results have been discordant. Furthermore, the role of inhaled corticosteroids (ICS) in COPD has not been extensively studied. A study was undertaken to evaluate vascular remodelling, its relationship with inflammatory cells and treatment effects in the bronchial mucosa of patients with COPD. Methods: The study comprised three groups: (1) 10 non-treated patients with COPD (COPD); (2) 10 patients with COPD treated with nebulised beclomethasone dipropionate 1600–2400 μg daily (equivalent to 800–1200 μg via metered dose inhaler) (COPD/ICS); and (3) 8 control subjects (CS). Bronchial biopsies were evaluated for number and size of vessels and vascular area. Specimens were also examined for vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and transforming growth factor β (TGF-β) expression and inflammatory cell counts were performed. Results: Vascular area, vessel size, VEGF+ cells, bFGF+ cells and TGF-β+ cells were significantly increased in the COPD group compared with the COPD/ICS and CS groups (all p<0.05). In addition, bFGF+ cells were significantly increased in the COPD/ICS group compared with the CS group, and CD8+ and CD68+ cells were significantly increased in the COPD group compared with the COPD/ICS and CS groups (p<0.05). In the COPD group the VEGF+ cells correlated with the number of vessels (p<0.05), vascular area (p<0.01) and vessel size (p<0.05), and TGF-β+ cells correlated significantly with vascular area (p<0.05). Conclusion: Bronchial vascular remodelling in patients with COPD is mainly related to morphological changes of the mucosal microvessels rather than to new vessel formation, and may be reduced in patients treated with steroids.